2020
DOI: 10.1097/ccm.0000000000004521
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Pandemic Measures: Reports From a National Survey of 9,120 ICU Clinicians

Abstract: Importance: Recent reports identify that among hospitalized coronavirus disease 2019 patients, 30% require ICU care. Understanding ICU resource needs remains an essential component of meeting current and projected needs of critically ill coronavirus disease 2019 patients. Objectives: This study queried U.S. ICU clinician perspectives on challenging aspects of care in managing coronavirus disease 2019 patients, current and anticipated resource demands, and personal stress. Design, Setting, and Participants: Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 4 publications
3
57
0
3
Order By: Relevance
“…ICU clinicians are obliged to wear personal protective equipment (PPE), including gloves, masks and gowns, due to the possibility of contamination [ 17 ]. Studies have shown the detrimental effects of isolation on patients (depression, anxiety and anger), and demonstrate that healthcare workers spent less time with patients in isolation [ 18 ].…”
Section: Personal Protective Equipment May Produce a Sense Of Depementioning
confidence: 99%
“…ICU clinicians are obliged to wear personal protective equipment (PPE), including gloves, masks and gowns, due to the possibility of contamination [ 17 ]. Studies have shown the detrimental effects of isolation on patients (depression, anxiety and anger), and demonstrate that healthcare workers spent less time with patients in isolation [ 18 ].…”
Section: Personal Protective Equipment May Produce a Sense Of Depementioning
confidence: 99%
“…6 Among patients who were discharged or died, the mortality rate of COVID-19 in this study was 4.5% of all hospitalized patients and 14% in ICU patients; however, this study is limited as no detailed patient information is available. Most hospitals suffered from lack of medical equipment, similar to other countries 7 . More than half of the flagship hospitals could provide only one N95 mask every 2 or more days.…”
Section: Discussionmentioning
confidence: 87%
“…A survey of ICU clinicians in the USA reported that shortages of PPE masks for medical staff were the most common issue. 7 The majority of hospitals worked diligently to ensure availability of medical supplies and PPE. After a quantity of the equipment was secured, some hospitals became concerned about the quality of the equipment.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of over 9000 ICU clinicians showed that both the perceived need for PPE masks (N95 respirators) (n = 2896, 38%) and ICU staffing shortages (n = 1614, 21.2%) exceeded all other resource challenges. All clinicians identified staff safety to minimize personal risk as the most challenging aspect of managing COVID‐19 patients in the ICU (respiratory therapists [45.2%], pharmacists [36.7%], physicians [35.7%], nurses [30.6%], and advanced practice providers [27.8%]) 21 . Pharmacy leadership should consider the potential impact and weigh the risks vs the benefits, including the availability of PPE, if removing pharmacists from in‐person rounding and direct patient care.…”
Section: Discussionmentioning
confidence: 99%